Analysis of postoperative effects of different semicircular canal surgical technique in patients with labyrinthine fistulas - Meng, Wei; Cai, Mingjing; Gao, Yanhui; Ji, Hongbo; Sun, Chuan; Li, Guangfei; Wei, Yanyan; Chen, Yan; Ni, Hui; Yan, Min; He, Shuangba (Frontiers in Neuroscience, 2022)
Objective: Different semicircular canal surgery techniques have been used to treat patients with labyrinthine fistulas caused by middle ear cholesteatoma. This study evaluated postoperative hearing and vestibular function after various semicircular canal surgeries. Materials and Methods: In group 1, from January 2008 to December 2014, 29 patients with middle ear cholesteatoma complicated by labyrinthine fistulas were treated with surgery involving covering the fistulas with simple fascia. In group 2, from January 2015 to October 2021, 36 patients with middle ear cholesteatoma complicated by labyrinthine fistulas were included. Cholesteatomas on the surface of type I labyrinthine fistulas were cleaned using the “underwater technique” and capped with a “sandwich” composed of fascia, bone meal, and fascia. Cholesteatomas on the surface of type II and III fistulas were cleaned using the “underwater technique,” and the labyrinthine fistula was plugged with a “pie” composed of fascia, bone meal, and fascia, and then covered with bone wax. Results: Some patients with labyrinthine fistulas in group 1 exhibited symptoms of vertigo after surgery. In group 2 Patients with type II labyrinthine fistulas experienced short-term vertigo after semicircular canal occlusion, but no cases of vertigo were reported during long-term follow-up. Hearing was not affected postoperatively in patients with type I labyrinthine fistulas capped with a “sandwich”. In patients with type II labyrinthine fistulas, the semicircular canal occlusion influenced postoperative hearing improvement. However, postoperative patient hearing was still superior to preoperative hearing. Conclusion: The surface of type I labyrinthine fistulas should be capped by a “sandwich” composed of fascia, bone meal, and fascia. Type II and III labyrinthine fistulas should be plugged with a “pie” composed of fascia, bone meal, and fascia, covered with bone wax.